Improve Writing Skill Description Text (Meningkatkan Keterampilan Menulis Teks Deskripsi) - Hesti Muliawati; Bela Nurzaman; Nina Oktaviani (Indonesian Language Education and Literature, 2018)
This research is motivated by the low interest of students writing the text of description on the students of Middle VII Middle-Class Farmers. To that end, the writer wanted to know the student activity in learning to write the description text by applying the problem-based learning method of the students of class VII of SMP Negeri 1 Tengah Tani, and to know the profile of writing the description text in the learning by using problem based on student VII SMP Negeri 1 Tengah Tani. Based on the result of a written test in this research, concluded that t count 2,23 and t table price 2.04 for 5% significance level, this means the application of a method of PBM in learning to write text description of the student of class VII of SMP Negeri 1 Tengah Tani effective. Meanwhile, the results of data observation in the form of student activity found that in the learning, established a good communicative relationship, in this case, the existence of an interaction between students with teachers, as well as students with other students. Profile writing text description of the students in grade VII SMP Negeri 1 Tengah Tani in learning by applying the PBM method has been very good, in this case, there is already an increase in test results between the initial test score with the final test score.Â Penelitian ini dilatarbelakangi oleh rendahnya minat siswa menulis teks deskripsi pada siswa SMP Negeri Tengah Tani Kelas VII. Untuk itu, penulis ingin mengetahui aktivitas siswa dalam pembelajaran menulis teks deskripsi dengan menerapkan metode pembelajaran berbasis masalah siswa kelas VII SMP Negeri 1 Tengah Tani, dan untuk mengetahui profil menulis teks deskripsi dalam pembelajaran dengan menggunakan berbasis masalah pada siswa VII SMP Negeri 1 Tengah Tani. Berdasarkan hasil tes tertulis dalam penelitian ini, menyimpulkan bahwa thitung 2,23 dan harga ttabel 2,04 untuk taraf signifikansi 5%, hal ini berarti penerapan metode PBM dalam pembelajaran menulis teks deskripsi siswa kelas VII SMP Negeri 1 Tengah Tani berlangsung efektif. Sementara itu, hasil dari observasi data berupa aktivitas siswa, didapat bahwa dalam pembelajaran tersebut, terjalin hubungan komunikatif yang baik, dalam hal ini sudah adanya interaksi antara siswa dengan guru, serta siswa dengan siswa lainnya. Profil menulis teks deskripsi siswa pada siswa kelas VII SMP Negeri 1 Tengah Tani dalam pembelajaran dengan menerapkan metode PBM sudah sangat baik, dalam hal ini sudah ada peningkatan hasil tes antara nilai tes awal dengan nilai tes akhir.